SIKAP MAHASISWA TERHADAP PEMBELAJARAN ALJABAR LINIER ELEMENTER DENGAN RECIPROCAL TEACHING - Erlinawaty . Simanjuntak (Universitas Negeri Medan, 2016)
ABSTRACTThis is a descriptive quantitative research with the aim to describe the attitudes of students using a scale of attitude. The population is all students S1 Mathematics Education Unimed 4th semester consists of 3 parallel classes. The sample was selected as one class. The collection of data through questionnaires to students. Data was analyzed by descriptive and inferential. Attitude scale used in this study to reveal the attitude of the students. The students' attitude with regard to the attitude (opinion) of students to group discussions, attitudes (opinions) of students to elementary algebra course, the attitude (opinion) regarding student learning with reciprocal teaching elementary algebra. This attitude scale consists of 25 statements, divided into 15 questions and 10 positive statements about the negative statement. The calculation result of the attitudes of students towards the three attitudes studied showed a positive attitude, an attitude seen scores of students were higher than scores a neutral stance. Based on the results of questionnaires that have been processed data can be stated that recriprocal teaching is one of the strategies that can increase the interest and ability of the students to discuss and express opinions.Keywords: Attitude Scale, Discussion and Reciprocal TeachingABSTRAKPenelitian ini bersifat deskriptif kuantitatif dengan tujuan untuk menguraikan tentang sikap mahasiswa menggunakan skala sikap. Populasi adalah seluruh mahasiswa S1 Pendidikan Matematika Unimed semester 4 yang terdiri dari 3 kelas pararel. Sampel dipilih sebanyak 1 kelas. Pengumpulan data melalui angket kepada mahasiswa. Data dianalisis secara deskriptif dan inferensial. Skala sikap dalam penelitian ini digunakan untuk mengungkap sikap mahasiswa. Sikap mahasiswa tersebut berkenaan dengan sikap (pendapat) mahasiswa terhadap diskusi kelompok, sikap (pendapat) mahasiswa terhadap mata kuliah aljabar elementer, sikap (pendapat) mahasiswa mengenai pembelajaran aljabar elementer dengan reciprocal teaching. Skala sikap ini terdiri dari 25 pernyataan yang terbagi atas 15 soal pernyataan positif dan 10 soal pernyataan negatif. Hasil perhitungan mengenai sikap mahasiswa terhadap ketiga sikap yang diteliti menunjukkan sikap yang positip, terlihat skor sikap mahasiswa yang lebih tinggi dari skor sikap netral. Berdasarkan hasil angket yang telah diolah datanya dapat dinyatakan bahwa recriprocal teaching merupakan salah satu strategi pembelajaran yang dapat meningkatkan minat dan kemampuan mahasiswa untuk berdiskusi dan mengemukakan pendapat. Kata Kunci: Skala Sikap , Diskusi dan Reciprocal Teaching